Determination of copper, zinc and manganese in nail and serum from patients with migraine - Özerol, E; Ulvi, H; Ilhan, N; Güleç, M; Ilhan, A; Akyol, Ö (Dustri-Verlag Dr Karl Feistle, 2003)
Metallo-enzymes contain trace elements in their molecular structure to be metabolically active. Manganese-superoxide dismutase (Mn SOD) contains Mn and copper, zinc-superoxide dismutase (Cu, Zn SOD) contains Cu. and Zn as prosthetic groups. There have been some studies on the oxidant/anti oxidant status of patients with migraine. In the present study, the levels of copper, zinc and manganese in nail and serum were investigated in 53 patients with migraine and 19 healthy subjects. Copper, Zn and Mn levels were measured by atomic absorption spectrophotometry and results obtained were statistically compared. The concentration of Mn in nail and serum was significantly higher in migraine patients than those of control subjects. Although Zn and Cu concentrations in nail were increased in migraine group compared to control group, the difference was not statistically significant. There was a statistically significant increase in Cu level (p < 0.02) and decrease in Zn level in serum from patients with migraine compared to those of control group. The unchanged or increased levels of trace elements, which play important roles as prosthetic groups in SOD, in both nail and serum may suggest that the antioxidant enzyme activities are not negatively affected from the changes. The results obtained are discussed in the light of the literature on the relationship between migraine and trace elements plus antioxidant systems.
2nd International Meeting on Free Radicals in Health and Disease -- MAY 08-12, 2002 -- ISTANBUL, TURKEY
Keywords: copper; manganese; migraine; nail; serum; zinc